2015
DOI: 10.1016/j.prnil.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for prostate cancer: Comparative studies including radical prostatectomy specimens and template transperineal biopsy

Abstract: PurposeMultiparametric magnetic resonance imaging (mpMRI) is an emerging technique aiming to improve upon the diagnostic sensitivity of prostate biopsy. Because of variance in interpretation and application of techniques, results may vary. There is likely a learning curve to establish consistent reporting of mpMRI. This study aims to review current literature supporting the diagnostic utility of mpMRI when compared with radical prostatectomy (RP) and template transperineal biopsy (TTPB) specimens.MethodsMEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Utilizing this technique with 12–18 cores is less time‐consuming, less costly and involves a reduced general anaesthesia time for the patient when compared with techniques aforementioned . Whilst access to specialist and radiology services is improving in Australian regional centres, there is a recognized discrepancy between Medicare‐funded services, health workforce and individual health status between rural and metropolitan areas …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing this technique with 12–18 cores is less time‐consuming, less costly and involves a reduced general anaesthesia time for the patient when compared with techniques aforementioned . Whilst access to specialist and radiology services is improving in Australian regional centres, there is a recognized discrepancy between Medicare‐funded services, health workforce and individual health status between rural and metropolitan areas …”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing debate about the reference standard to which mpMRI is compared. 34 A systematic review found that ‘various authors advocate comparing MRI with transrectal biopsy, TPB or prostatectomy specimens’ but concluded that even studies which compared both biopsy and RP specimens to MRI produced similar results, a high negative predictive value of MRI specimens …”
Section: Discussionmentioning
confidence: 99%
“…The fact that the PI-RADS criteria were updated 3 years ago further accentuates the difficulty with standardizing radiologic interpretation of prostate MRI. Other authors have emphasized that it is difficult to differentiate between the individual impact of urologists, radiologists, and institutions on detection of PCa [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Currently MRI-targeted biopsy has been reported to be useful in detection of evasive anterior tumors15. A review of current literature supporting utility of multi-parametric MRI (mpMRI) showed the sensitivity of mpMRI for PCa detection to be 80–90% and the specificity for suspicious lesion to be between 50% and 90%16. Despite a growing body of literature, debate over capability of mpMRI in reliably detecting significant cancer still remains17.…”
Section: Discussionmentioning
confidence: 99%